Real-world study of overall survival with palbociclib plus aromatase inhibitor in HR+/HER2− metastatic breast cancer - Hope S. Rugo; Adam Brufsky; Xianchen Liu; Benjamin Li; Lynn McRoy; Connie Chen; Rachel M. Layman; Massimo Cristofanilli; Mylin A. Torres; Giuseppe Curigliano; Richard S. Finn; Angela DeMichele (npj Breast Cancer, 2022)
Abstract Data on real-world effectiveness of cyclin-dependent kinase 4/6 inhibitor combination therapy versus endocrine therapy alone are limited. The Flatiron Health Analytic Database was used to assess overall survival (OS) in patients with hormone receptor–positive/human epidermal growth factor receptor 2–negative (HR+/HER2−) metastatic breast cancer (MBC) treated with first-line palbociclib plus an aromatase inhibitor (AI) versus an AI alone in routine US clinical practice. In total, 2888 patients initiated treatment during February 3, 2015–March 31, 2020, with a potential ≥6-month follow-up (cutoff date, September 30, 2020). After stabilized inverse probability treatment weighting, median OS (95% CI) is significantly longer among palbociclib versus AI recipients (49.1 [45.2–57.7] versus 43.2 [37.6–48.0] months; hazard ratio, 0.76 [95% CI, 0.65–0.87]; P < 0.0001). Progression-free survival (95% CI) is 19.3 (17.5–20.7) versus 13.9 (12.5–15.2) months, respectively (hazard ratio, 0.70 [95% CI, 0.62–0.78]; P < 0.0001). These data support first-line palbociclib plus an AI treatment for HR+/HER2− MBC. (Trial number NCT05361655).